Pension reform in Georgia - how to do it well - Panchvidze, Natia; Klazar, Stanislav, 1974-; Trgiňa, Gejza; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
This research examines ways in which pensions and pensions system reform could impact the future economic development of Georgia. It analyses current pension structure and outlines how it could be used to develop a new structure with the goal to improve the financial position of the elderly and to provide means to achieve broader economic growth.Existing pension system in Georgia includes state pension or PAYG (unfunded) pension program and non-state pension funds or voluntary pension schemes. Because of Georgia’s fiscal constraints and aging population, there is a need for creating a mandatory savings pension System. The objective of the pension reform is to create a new system that requires automatic participation of formally employed individuals who earn monthly minimum of 500 GEL and who are between ages of 15 and 45.As the paper focuses on the reform of Georgia’s old age pension system, it examines the features, operations and functioning of a mandatory savings pension and analyses how Georgia’s present and evolving future structure might resemble the World Bank’s multi-pillar approach. Based on the current Georgia’s economic, demographic and pension system the paper suggests that the introduction of a defined-contribution mandatory occupational system deserves consideration.
Vedoucí práce: Stanislav Klazar
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses